6 kW Single Stage Narrow Linewidth Fiber Amplifier Based on the Balance Between Mode Instability and Nonlinear Effects - Xin Tian; Binyu Rao; Meng Wang; Xiaoming Xi; Baolai Yang; Zilun Chen; Hu Xiao; Xiaolin Wang; Pengfei Ma; Zefeng Wang; Jinbao Chen (IEEE Photonics Journal)
Single-stage high-power narrow-linewidth fiber laser has been investigated intensively recently because of its simple and robust configuration and great potential in spectral/coherent beam combination. In this work, a 6 kW narrow-linewidth fiber amplifier was experimentally achieved based on a fiber oscillator seed. By employing a few-mode ytterbium-doped fiber, the spectral broadening and SRS effects are both significantly mitigated. Combined with a wavelength-stabilized 981 nm pump source, the threshold of transverse mode instability is improved, then, a maximum output power of 6020 W at the central wavelength 1080 nm was achieved with 3-dB bandwidth of ∼0.37 nm and optical-to-optical efficiency of ∼85.6%. The mode instability and nonlinear effects were balanced well. The measured beam quality and the signal to Raman ratio were M2∼2.7 and ∼27 dB, respectively. This work shows the great potential of such amplification structure for the power scaling of high-power narrow-linewidth fiber lasers.